Variations in GP–patient communication by ethnicity, age, and gender: evidence from a national primary care patient survey - Burt, Jenni (Br J Gen Pract, 2016)
BACKGROUND: Doctor–patient communication is a key driver of overall satisfaction with primary care. Patients from minority ethnic backgrounds consistently report more negative experiences of doctor–patient communication. However, it is currently unknown whether these ethnic differences are concentrated in one gender or in particular age groups. AIM: To determine how reported GP–patient communication varies between patients from different ethnic groups, stratified by age and gender. DESIGN AND SETTING: Analysis of data from the English GP Patient Survey from 2012–2013 and 2013–2014, including 1 599 801 responders. METHOD: A composite score was created for doctor–patient communication from five survey items concerned with interpersonal aspects of care. Mixed-effect linear regression models were used to estimate age- and gender-specific differences between white British patients and patients of the same age and gender from each other ethnic group. RESULTS: There was strong evidence (P<0.001 for age by gender by ethnicity three-way interaction term) that the effect of ethnicity on reported GP–patient communication varied by both age and gender. The difference in scores between white British and other responders on doctor–patient communication items was largest for older, female Pakistani and Bangladeshi responders, and for younger responders who described their ethnicity as ‘Any other white’. CONCLUSION: The identification of groups with particularly marked differences in experience of GP–patient communication — older, female, Asian patients and younger ‘Any other white’ patients — underlines the need for a renewed focus on quality of care for these groups.